The Impactof PT PLN Tanjung Jati B's Corporate Social Responsibility on the Welfare of Micro, Small and Medium Enterprises - Muhammad Yasin; Fatchur Rohman (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
Corporate Social Responsibility (CSR) is a responsibility towards the environment in realizing the social welfare of the community. This study aims to determine the effect of the CSR of PT. PLN Tanjung Jati B on the welfare of the UMKM under its guidance. CSR indicators are the goals of corporate social responsibility (X1), corporate social issue (X2), corporate relations programs (X3) and the welfare of MSMEs (Y).This study uses primary data in the form of data obtained directly in the field, the research sample is 47 MSME CSR respondents guided by PT. PLN Tanjung Jati B 2019. The sampling technique used was simple random sampling. The study was conducted using questionnaires and interviews, the data analysis method used was quantitative method with multiple linear regression analysis approach.In a small scope, based on the results of the T Test (Partial Test), partially the corporate social responsibility goal variable (X1) from tcount 2,300> ttable 1,68107 shows that the goals of corporate social responsibility have a significant positive effect on the welfare of MSMEs. In corporate social problems (X2) from tcount 1.087 <ttable 1.68107 it shows that corporate social issue have a positive and insignificant effect on the welfare of MSMEs and in the corporate relations program variable (X3) from tcount 2.108> ttable 1.68107 shows that the company relations program has an effect significantly positive on the welfare of MSMEs. Meanwhile, the F test (Simultaneous Test) proves that the objectives of corporate socialresponsibility goal, corporate social issue, and the corporate relations program of PT. PLN Tanjung Jati B significantly affects the welfare of MSMEs by 14,445%.